Sistem Pendukung Keputusan Dalam Menentukan Kelayakan Kredit Pembelian Mobil Dengan Metode TOPSIS - Paulus Hendrico Silalahi; Saifullah Saifullah; Irfan Sudahri Damanik (STMIK Budi Darma, 2021)
Four-wheeled vehicles become the needs of society is quite important at this time, can be seen from the density of traffic every day. Type of four-wheeled vehicles are also very varied, among others, Honda, Izusu, Toyota, Mazda, and many more, therefore there are still many people who are confused when wanting to buy a car. People who want to buy a car also often ask for help or advice from others to choose what car is suitable for the buy. Many aspects must be considered in buying a car, then people who are often confused to choose because it is faced with the large selection of types of cars in the Sorum. I am here to provide a short solution how to choose a car that according to the will and our individual tastes using the method.